Modulation of axonal signalling in type 1 episodic ataxia. (25th February 2016) - Vivekananda, Umesh; Novak, Pavel; Volynski, Kirill; Kullmann, Dimitri
Abstract: Background: Type 1 episodic ataxia is a disorder characterised by paroxysmal cerebellar incoordination and interictal myokymia. It is caused by dominant negative mutations of KCNA1, which encodes the presynaptic and axonal potassium channel subunit Kv1.1. Mutations in the disorder increase neuronal excitability and neurotransmitter release in neuronal cultures. Our hypothesis is that type 1 episodic ataxia prolongs the action potential at presynaptic terminals thus causing increased neurotransmitter release. We aimed to test this hypothesis in mouse models of type 1 episodic ataxia. Methods: We used two mouse models, one with a knockout of the KCNA1 mutation ( KCNA1a –/–) and one with a knockin of the mutation KCNA1a (V408A/+). We used scanning ion conductance microscopy to acquire super-resolution images of very small synaptic boutons (∼1 μm diameter) in mouse hippocampal neuronal cultures and achieved direct electrophysiological recording from these boutons. We compared wild-type, KCNA1a –/–, and KCNA1a (V408A/+) mice. Action potentials were either elicited by injection of a depolarising current at the bouton or via a second pipette at the cell body. Findings: Presynaptic action potential half width was larger in KCNA1a –/– mice than in their wild-type littermates when directly elicited at the bouton (mean 1·43 ms [SE 0·12] vs 0·86 [0·068]) and when elicited by depolarising the cell body (1·44 [0·089] vs 1·17 [0·055]), and was also larger in KCNA1a (V408A/+) mice (1·14 [0·063] vs 0·91 [0·065] and 1·38 [0·063] vs 1·11 [0·048], respectively). In separate prepulse experiments, wild-type mice showed an increase in bouton action potential half width when moving from hyperpolarising to depolarising subthreshold prepulse steps. KCNA1a –/– mice also showed increasing action potential half widths with the steps. However, in KCNA1a (V408A/+) mice this positive correlation was abolished. Interpretation: A prolonged presynaptic action potential in type 1 episodic ataxia might cause the increase in neurotransmitter release. Progressive presynaptic depolarisation in KCNA1a (V408A/+) mice has no effect on Kv1.1 inactivation, which in turn might affect the digital-analogue facilitation of synaptic transmission in hippocampal synapses. Since Kv1.1 is abundantly expressed in cerebellar basket cells, it could lead to added inhibition of cerebellar Purkinje cells and ataxia. Funding: Wellcome Trust.